(untitled) (Experimental biology, 2016)
The comparative analysis of quantitative and qualitative composition of saprophytic and conditionally pathogenic microorganisms of fish Kapshagai NVH when it is feeding different types of feeds. Study of TMN bodies trout and tilapia with its feeding different fodder productional showed a slight excess of indicators of contamination of its organs in pre-production versions. In General, the study of the cultural-morphological properties discovered and cultures of bacteria found that microorganisms like trout and tilapia represented moving and not moving, gram-positive and gram-negative cocci and sticks. It should be noted the dominance in the microflora of fish moving gram-negative bacteria (sticks), which represents more than 50% of the total microbial background. Found that the microflora as trout and tilapia represented saprofitnymi and opportunistic bacteria genera Lactobacillus, TB test Sarcina, Micrococcus, Staphylococcus, Pseudomonas, Aeromonas, Bacillus, Proteus, Vibrio, E., Serratia, Hafnia, Enterobacter, Clostridium, Spirillum.